S2e-Leitlinie: Therapie der rheumatoiden Arthritis mit krankheitsmodifizierenden Medikamenten = S2e guideline: treatment of rheumatoid arthritis with disease-modifying drugs - Fiehn, Christoph; Holle, J.; Iking-Konert, C.; Leipe, J.; Weseloh, C.; Frerix, M.; Alten, R.; Behrens, F.; Baerwald, C.; Braun, J.; Burkhardt, H.; Burmester, G.; et al. (Zeitschrift für Rheumatologie, 2018)
BACKGROUND: Medication-based strategies to treat rheumatoid arthritis are crucial in terms of outcome. They aim at preventing joint destruction, loss of function and disability by early and consistent inhibition of inflammatory processes. - OBJECTIVE: Achieving consensus about evidence-based recommendations for the treatment of rheumatoid arthritis with disease-modifying anti-rheumatic drugs in Germany. - METHODS: Following a systematic literature research, a structured process among expert rheumatologists was used to reach consensus. - RESULTS: The results of the consensus process can be summed up in 6 overarching principles and 10 recommendations. There are several new issues compared to the version of 2012, such as differentiated adjustments to the therapeutic regime according to time point and extent of treatment response, the therapeutic goal of achieving remission as assessed by means of the simplified disease activity index (SDAI) as well as the potential use of targeted synthetic DMARDs (JAK inhibitors) and suggestions for a deescalating in case of achieving a sustained remission. Methotrexate still plays the central role at the beginning of the treatment and as a combination partner in the further treatment course. When treatment response to methotrexate is inadequate, either switching to or combining with another conventional synthetic DMARD is an option in the absence of unfavourable prognostic factors. Otherwise biologic or targeted synthetic DMARDs are recommended according to the algorithm. Rules for deescalating treatment with glucocorticoids and-where applicable-DMARDs give support for the management of patients who have reached a sustained remission. - DISCUSSION: The new guidelines set up recommendations for RA treatment in accordance with the treat-to-target principle. Modern disease-modifying drugs, now including also JAK inhibitors, are available in an algorithm.
Gesehen am 17.04.2020